The impact of artificial intelligence on the formation and the development of the law - Lafrance, Sébastien (Đại học Quốc gia Hà Nội, 2020)
Artificial intelligence and its impact on the law are in constant evolution. In that field, dreams about the future, reflected by science-fiction movies, and the reality are sometimes, and become more and more nowadays, the same thing. However, they should not, for the most part, be conflated. Singularity, where technology changes so much that it becomes more intelligent than humans, will not be soon at our door. The author examines how the evolution of the law is impacted by artificial intelligence. He also discusses what law should be applicable to robots. This is an original contribution with a Canadian perspective to this topic.